Portrayal Of Women In Nigerian News Magazine - Ifeoma, Ojiakor; Adeline, Nkwam-Uwaoma; Tubo, Victor; Fabian, Okalla (Advances in Social Sciences Research Journal, 2018)
News stories and items have contributed to the subjugation of one sex while increasing the visibility of the other. The way and manner gender is represented have been and will continue to be a subject of discursive struggle between pro-feminists and anti-feminists. However, most studies seem to concentrate on newspapers and advertisements using pictures and images as units of analysis at the near exclusion of news magazines and news stories. This has necessitated having the beam light on news magazines and specifically on news stories. This study therefore examined Tell and The News magazine to ascertain the portrayal of women in the news and consequently formed research questions to test the invisibility and under representativeness of women in Nigeria news. Using content analysis of the sampled magazine from January 2014 to June 2014, the study found out amongst other things that women are underrepresented in the news as subject and reporters. Also, the work is linked to media framing theory which posits that the way the media selects some aspects of a perceived reality and makes them more salient in a communication text, promotes a particular problem definition, causal interpretation, moral evaluation, and/or treatment recommendation for the item described”. The paper therefore recommends increased visibility of women in the media through training of communication teachers and incorporating gender course in schools and also doggedness when the going gets tough as expected.